Bermuda : Assessment of the Supervision and Regulation of the Financial Sector-Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2005)
This paper assesses the financial sector regulation and supervision in Bermuda in the context of the offshore financial center assessment program. The assessment reveals that the financial, regulatory, and supervisory framework is well developed in banking, the key areas of securities regulation, and antimoney laundering and combating the financing of terrorism (AML/CFT). Banking supervision is largely in conformity with the Basel Core Principles. The regulation of investment intermediaries and collective investment schemes, the main activities of the Bermudian securities industry, is working effectively. However, some deficiencies were noted in the assessment of insurance.